Systematic Review and Meta-Analysis of Fear of COVID-19 - Luo, Faxiang; Ghanei Gheshlagh, Reza; Dalvand, Sahar; Saedmoucheshi, Sholeh; Li, Qingyun (Frontiers in Psychology, 2021)
Background: Due to lack of preparedness of health systems, fast spread of the new virus, high mortality rates, and lack of a definite treatment, the outbreak of Covid-19 led to high levels of fear and anxiety in different populations. In addition, isolation, mental disorders, and limitations in social interactions as a result of lockdown and travel ban increased the fear of the new coronavirus. Methods: International databases, including Scopus, PubMed, Web of Science, Google scholar were searched without any time limitation, and all observational studies published in English reporting the mean of fear of Coronavirus disease (COVID-19) based on the Fear of COVID-19 scale (FCV-19S) were included in the analysis. Methodological quality was assessed using the Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines. Random effects model, subgroup analysis, and meta-regression analysis were used to analyze the data. Heterogeneity across studies was examined using Cochran's Q test and I2 statistic. All the statistical analyses were conducted using R software v4.0.3. Results: A total of 44 articles with a sample size of 52462 were reviewed. A pooled mean of 18.57 was found for fear of Covid-19. The mean of fear of Covid-19 was higher in women than in men (20.67 vs. 18.21). The highest and lowest means of fear of Covid-19 had been found in ASIA (18.36) and Australia (17.43) based on continent, and in hospital staff (19.51) and college students (17.95) based on target population, respectively. In addition, the highest and lowest means of fear of Covid-19 were related to items #1 and #3 of the scale, respectively. According to the results of meta-regression analysis, there was no significant association between the mean of fear of Covid-19 and sample size and participants’ age. In addition, publication error was not significant (P=0.721). Conclusion: The mean of fear of COVID-19 was high around the world; therefore, it seems necessary to pay more attention to the negative effects of the COVID-19 pandemic on mental health.